Fully Automated Production of (((S)-1-Carboxy-5-(6-([18F]fluoro)-2-methoxynicotinamido)pentyl)carbamoyl)-l-glutamic Acid ([18F]JK-PSMA-7) - Philipp Krapf; Thomas Wicher; Boris D. Zlatopolskiy; Johannes Ermert; Bernd Neumaier (Pharmaceuticals)
Background: The radiotracer [18F]JK-PSMA-7, a prostate cancer imaging agent for positron emission tomography (PET), was previously synthesized by indirect radiofluorination using an 18F-labeled active ester as a prosthetic group, which had to be isolated and purified before it could be linked to the pharmacologically active Lys-urea-Glu motif. Although this procedure could be automated on two-reactor modules like the GE TRACERLab FX2N (FXN) to afford the tracer in modest radiochemical yields (RCY) of 18–25%, it is unsuitable for cassette-based systems with a single reactor. Methods: To simplify implementation on an automated synthesis module, the radiosynthesis of [18F]JK-PSMA-7 was devised as a one-pot, two-step reaction. The new method is based on direct (“late-stage”) radiofluorination of an appropriate onium triflate precursor and subsequent deprotection with ortho-phosphoric acid. It was successfully established on the cassette-based Trasis AllInOne (AIO) module. Results: Overall, the new protocol enabled the production of [18F]JK-PSMA-7 in activity yields of 39 ± 4% (RCY = 58%) with an overall synthesis time of about 1 h. In a single production run with an initial activity of 36-43 GBq, 13-19 GBq of [18F]JK-PSMA-7 with a radiochemical purity of >99% was obtained. Conclusions: We have established a highly reliable, GMP-compliant process for the automated radiosynthesis of [18F]JK-PSMA-7 on the Trasis AllinOne (AIO) synthesizer, ensuring consistent and efficient production of this radioligand.